2009
DOI: 10.5465/amp.2009.45590137
|View full text |Cite
|
Sign up to set email alerts
|

What's the Evidence on Evidence-Based Management?

Abstract: In this article, we respond to recent calls for increased use of evidence-based management (EBMgt) by conducting a systematic review of the literature to answer the following questions: (1) Is there a substantial literature concerning the concept of evidence-based management? (2) What is the quality of evidence (where it exists) regarding evidence-based management? and (3) Is there evidence that employing evidence-based management will improve organizational performance? We applied an assessment rubric based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(109 citation statements)
references
References 22 publications
3
93
0
6
Order By: Relevance
“…but even this implies cognition rather than instinct, intuition and sub-conscious and this more 'reflex-based' decision-taking. This finding therefore supports comments in the EBM literature suggesting less importance was being given in the EBM debate to other aspects of managerial decision-making, such as instinct, intuition and experience (Harrison, 1998;Marks, 2002;Learmonth and Harding, 2006;Rousseau, 2006;Arndt and Bigelow, 2007;Morrell, 2008;Reay et al, 2009;Hovmand and Gillespie, 2010) and supports the suggestions in the decision-making literature of the importance of intuition for strategic managers (Hodgkinson, et al, 2009).…”
Section: Emergent Decision-making In Collaboration With Others Notabsupporting
confidence: 79%
See 3 more Smart Citations
“…but even this implies cognition rather than instinct, intuition and sub-conscious and this more 'reflex-based' decision-taking. This finding therefore supports comments in the EBM literature suggesting less importance was being given in the EBM debate to other aspects of managerial decision-making, such as instinct, intuition and experience (Harrison, 1998;Marks, 2002;Learmonth and Harding, 2006;Rousseau, 2006;Arndt and Bigelow, 2007;Morrell, 2008;Reay et al, 2009;Hovmand and Gillespie, 2010) and supports the suggestions in the decision-making literature of the importance of intuition for strategic managers (Hodgkinson, et al, 2009).…”
Section: Emergent Decision-making In Collaboration With Others Notabsupporting
confidence: 79%
“…However, given its specific inclusion of individuals who were currently studying for an MBA, this study might suggest that it is not necessarily the 'lacking of shared scientific knowledge' that is the reason, but simply that preference is given to intuition and peer collaboration. The finding that intuition was the most ('currently studying sample'), or second-most ('general sample') form of evidence again provides support for the literature that claims that instinct, intuition and experience are (wrongly) given less importance than the more positivist, quantitative types of research evidence in the EBM literature (Harrison, 1998;Marks, 2002;Learmonth and Harding, 2006;Rousseau, 2006;Arndt and Bigelow: 2007;Morrell, 2008;Reay et al, 2009;Hovmand and Gillespie, 2010) and that the more recent, broader conceptualisation of EBM (Briner et al, 2009) is more appropriate. The findings from this study also suggest that the Briner framework might usefully be extended to include 'peer expertise and judgement' and 'personal values'.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Rynes, Giluk, and Brown (2007) showed that HR practitioner and "bridge" journals failed to report some of the most significant HR research reported in peer-reviewed academic journals and, where they did, studies were often misrepresented. A study by Reay, Berta, and Kohn (2009) which sought to locate "the evidence" for evidence-based management concluded that "the literature has yet to move much beyond . .…”
mentioning
confidence: 99%